Corporate Investment Incentives and Accounting‐Based Debt Covenants* - Douglas, Alan V. S. (Contemporary Accounting Research, 2003)
Abstract This paper studies the conditions under which accounting‐based debt covenants increase firm value in a setting that incorporates the conflicting incentives of shareholders, bondholders, and managers. We construct a model in which debt is needed to discipline managerial investment decisions despite endogenous compensation contracts. We show that accounting covenants increase value when (1) debt serves as a credible commitment to penalize poor investment decisions; (2) the firm faces other (exogenous) sources of uncertainty that can make debt risky despite good investment decisions; and (3) accounting information serves as a contractible proxy for firm's economic performance. In these circumstances, accounting covenants ensure that shareholders do not offer compensation schemes that would encourage bondholder wealth expropriation when the debt becomes risky. A covenant specifying a required level of accounting performance provides additional bondholder power when performance is low. An accounting‐based dividend covenant allows a disbursement to maintain investment incentives when performance is high without allowing dividend‐based expropriation. The optimal covenants depend on the reliability of accounting information, and the interaction between accounting performance and the different incentive conflicts provides new insight into the empirical literature on accounting‐based covenants.